Supplementation of maize stover for Ethiopian Menz sheep: effects of cottonseed, noug (Guizotia abyssinica) or sunflower cake with or without maize on the intake, growth, apparent digestibility, nitrogen balance and excretion of purine derivatives - Osuji, P.O.; Sibanda, S.; Nsahlai, I.V. (1993)
Thirty-six male Ethiopian Menz sheep, given maize stover supplemented with either cottonseed cake, noug cake or sunflower cake with or without maize grain, were used in an 88-day study comprising growth and balance trials. There was no significant interactions. Sheep consumed significantly more stover when supplemented with CSC compared with NGC and SFC. Maize grain significantly increased organic matter intake. Although CSC tended to support lower live-weight gains, the effect of protein was not significant. Maize grain increased live-weight gains. Urinary Nitrogen excretions were similar between CSC and SFC but about 0.22 higher with NGC. The faecal N output was 0.33 and 0.18 higher with CSC than with NGC and SFC respectively. Maize grain has no effect on any of the N-balance measurements. Cottonseed cake supported lower daily production of purine derivatives, microbial purine and microbial protein than either NGC or SFC. Maize grain increased the daily excretion of total PD, microbial purine and microbial protein. Neither the protein source nor maize grain affected the efficiency of microbial protein synthesis. It was concluded that SFC was utilized more effectively both in terms of rumen microbial N synthesis, N retention and growth. The addition of a small amount of energy as crushed maize grain increased microbial N synthesis, N retention and live-weight gain.